A case of hepatic portal venous gas that resolved with conservative treatment. Issue 1 (12th November 2020) - Kogo, Hideki; Takasaki, Hideaki; Sakata, Yoshinori; Nakamura, Yoshiharu; Yoshida, Hiroshi
Abstract: Hepatic portal venous gas (HPVG) is a potentially fatal condition. If vital signs are normal and laboratory data are not suggestive of any necrotic changes, a follow‐up computed tomography after a conservative procedure can be performed at short intervals to conservatively monitor the patient. Abstract : Hepatic portal venous gas (HPVG) is a potentially fatal condition. If vital signs are normal and laboratory data are not suggestive of any necrotic changes, a follow‐up computed tomography after a conservative procedure can be performed at short intervals to conservatively monitor the patient.